Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Sum the series:
$$1 + \dfrac13 \cdot \dfrac14 + \dfrac15 \cdot \dfrac1{4^2} + \dfrac17 \cdot \dfrac1{4^3} + \cdots$$

How can I solve this? I am totally stuck on this problem.

share|cite|improve this question
up vote 7 down vote accepted

Let $$S = \sum_{n=0}^{\infty} \dfrac1{2n+1} \dfrac1{4^n}$$ Note that $$\dfrac1{2n+1} = \int_0^1 x^{2n} dx$$ Hence, we can write \begin{align} S & = \sum_{n=0}^{\infty} \dfrac1{4^n}\int_0^1 x^{2n} dx = \int_0^1 \sum_{n=0}^{\infty} \left(\dfrac{x^2}{4} \right)^n dx\\ & = \int_0^1 \dfrac{dx}{1-\dfrac{x^2}4} = \int_0^1 \dfrac{dx}{2-x} + \int_0^1 \dfrac{dx}{2+x}\\ & = \left. -\log(2-x) \right \vert_0^1 + \left. \log(2+x) \right \vert_0^1 = \log 3 \end{align} Hence, $$\sum_{n=0}^{\infty} \dfrac1{2n+1} \dfrac1{4^n} = \log(3)$$

share|cite|improve this answer
swapping a term for an equivalent definite integral is unintuitive at least, replacing a simpler term with a more complex term that requires evaluation should make things harder not easier. But as this example shows the opposite is true, do you know of any more similar type of examples? (i.e. making progress by introducing more complexity ) – Arjang Jan 13 '13 at 6:29
@Arjang There are tons of examples like this. Any sum of the form $\sum_{n=1}^{\infty} P(n) x^n$ where $P(n)$ is a polynomial in $n$ or one over a polynomial in $n$ is amenable to this technique. You may want to look at this problem solved yesterday, where a complex sum is easily solved in terms of an integral. – user17762 Jan 13 '13 at 6:37

Using Infinite geometric series, $$1+x+x^2+\cdots=\frac1{1-x}$$ for $|x|<1$

Applying integration wrt to $x, \log(1-x)=-x-\frac{x^2}2-\frac{x^3}3+\cdots+c$ where $c$ is an arbitrary constant of indefinite integral.

Putting $x=0,\log(1)=c\implies c=0$

So, $$\log(1-x)=-x-\frac{x^2}2-\frac{x^3}3+\cdots$$

Putting $x=y$ we get, $$\log(1-y)=-y-\frac{y^2}2-\frac{y^3}3+\cdots$$

Putting $x=-y$ we get, $$\log(1+y)=y-\frac{y^2}2+\frac{y^3}3+\cdots$$

So, $$\log(1+y)-\log(1-y)=2(y+\frac{y^3}3+\frac{y^5}5+\cdots)$$ for $|y|<1$

Consequently, $$1 + \dfrac13 \cdot \dfrac14 + \dfrac15 \cdot \dfrac1{4^2} + \dfrac17 \cdot \dfrac1{4^3} + \cdots=2\left(\frac12+\frac{\left(\frac12\right)^3}3+\frac{\left(\frac12\right)^5}5+\cdots\right)$$ $$=\log(1+\frac12)-\log(1-\frac12)=\log\left(\frac{\frac32}{\frac12}\right)=\log 3$$

share|cite|improve this answer
@Arjang, how much is the complexity of this? – lab bhattacharjee Jan 13 '13 at 18:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.